English Teaching Challenges at IAIN Kudus in Millennial Era - Setyaningrum, Anisah (Institut Agama Islam Negeri Kudus, 2020)
This study is a qualitative descriptive research which aimed at exploring the challenges and strategies in teaching English at IAIN Kudus in millennial era. The informants of this research were the English lecturers in IAIN Kudus and the third semester students of English Study Program Tarbiyah Faculty of IAIN Kudus. The result of this study showed that the English lecturers faced some challenges in teaching English at IAIN Kudus in Millennial era. The challenges were related to technology, personal behaviors, mentoring, and communication. In facing those challenges, the English lecturers applied some strategies such as determining the specific time in accessing technology during the class, determining the allowed and unallowed attitudes that can be done in the process of English teaching-learning, giving mentoring to the students, and creating good communication with the students.